2022
DOI: 10.1108/febe-05-2022-0018
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of construction workers’ mental health before and during COVID-19 pandemic in Nigeria

Abstract: PurposeBecause of the sort of working environment and the nature of construction jobs, a high rate of poor mental health has been recorded in the construction industry. The aim of this study is to compare construction workers' mental health before and during the COVID-19 pandemic in Nigeria.Design/methodology/approachA survey questionnaire was developed and administered online to building environment professionals working on construction sites. Data were analysed using descriptive statistics such as mean and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Laborers' hourly wage structures meant they needed to be physically present on-site, both before and after the pandemic, and the fear of contracting the virus from colleagues created a sense of panic and concern about their health status and job stability. This fear of losing their source of income further exacerbates their stress and anxiety during these challenging times [4,47,[55][56][57]. On the other hand, managers, being able to work remotely, were able to minimize their human contact, reducing their exposure to the virus and potential health risks.…”
Section: Discussionmentioning
confidence: 99%
“…Laborers' hourly wage structures meant they needed to be physically present on-site, both before and after the pandemic, and the fear of contracting the virus from colleagues created a sense of panic and concern about their health status and job stability. This fear of losing their source of income further exacerbates their stress and anxiety during these challenging times [4,47,[55][56][57]. On the other hand, managers, being able to work remotely, were able to minimize their human contact, reducing their exposure to the virus and potential health risks.…”
Section: Discussionmentioning
confidence: 99%
“…Creating a safe workplace is another crucial strategy for health and safety (Oni et al ., 2022b). Maintaining a safe workplace is critical for lowering the risk of worker injuries.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Furthermore, the routes to this goal are fraught with dangers to workers' lives. Construction workers have been involved in a variety of accidents over the years due to the nature of the work, and these can be attributed to worker and employer negligence or ignorance (Oni et al ., 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…A critical analysis of the 54 PPGCI articles reviewed in this paper revealed that four distinct PP themes were investigated, and these are presented in Figure 3. that Covid-19 had a significant negative impact on project performance in the construction industry, with the main impacts being reduced worker productivity (Al-Mhdawi et al, 2023;Oni et al, 2023;Wijayaningtyas et al, 2022), scarcity and cost increases of building materials due to supply chain disruptions (Alhammadi, 2022;Farooq et al, 2022;Gumusburun Ayalp & Çivici, 2022) and poor cash flows due to scarcity of construction projects during the pandemic (Oladimeji, 2022;Sami Ur Rehman et al, 2022;Tekin, 2022).…”
Section: Themes Investigated By Ppgci Articles During the Covid-19 Er...mentioning
confidence: 99%